Effect of post-weld heat treatment on dissimilar AA2014-AA5083 friction stir welded joints - Vipin Sharma; Mohit Pramod Sharma; Anuj Kumar Jain (Journal of Alloys and Metallurgical Systems)
In this study the AA2014-AA5083 alloys are friction stir welded at two different rotational speeds of 1400 and 1000 rpm with constant welding speed of 63 mm/min. To investigate the microstructural thermal stability of welded joints post-weld heat treatment is conducted at 573 K, 673 K, 773 K and 823 K. The welded specimen showed thermal stability up to 673 K in both the conditions. At higher temperatures, the low rotational speed specimen showed the abnormal grain growth. On the other hand, the specimen welded at 1400 rpm showed location dependent and limited abnormal grain growth. Specimens welded at 1000 rpm exhibited lower tensile strength and ductility than those welded at 1400 rpm due to abnormal grain growth.